AESTHETIC FEATURES OF THE STRUCTURE OF THE FACES IN CHILDREN WITH DENTAL AND FACIAL ANOMALIES ІІ1 CLASS BY ENGLEM AND IMPAIRED NASAL BREATHING ACCORDING TO PHOTOMETRY - N.V. Golovko (Український стоматологічний альманах)
The habit of mouth breathing may be due to a variety of functional and organic disorders and is caused by three factors: impaired function of muscles, locking the mouth, obstacles in the upper respiratory tract, mouth breathing habit that remained after removing the cause of nasal obstruction as reflex.